2010
DOI: 10.1021/op1000308
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Optically Active β-Amino-α-methylene Carbonyl Derivatives From α-Amidosulfones Using Quinine-Based Phase-Transfer Catalysts

Abstract: Optically active β-amino-α-methylene carbonyl derivatives (aza-Morita−Baylis−Hillman adducts) were prepared using a one-pot protocol involving an enantioselective Mannich reaction catalyzed by various quinine-based catalysts, followed by a Horner olefination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
1
Order By: Relevance
“…[125] Optically active b-amino-a-methylene derivatives (aza-Morita-Baylis-Hillman adducts), such as 158, were prepared by using a one-pot protocol involving the enantioselective Mannich reaction of 157 catalyzed by 2 n, followed by a Horner olefination (Scheme 97). [126] Jørgensen and co-workers reported an asymmetric monofluorovinylation through an enantioselective Mannich reaction of a-fluoro-b-keto-benzothiazolesulfone, such as 159, with in situ generated N-benzyloxycarbonylimine (N-Cbz-imine) in the presence of catalyst 2 o. Reduction of the Mannich product with LiBH 4 gave (E)-160 with good enantioselectivity (Scheme 98).…”
Section: à C Bond Formationmentioning
confidence: 99%
“…[125] Optically active b-amino-a-methylene derivatives (aza-Morita-Baylis-Hillman adducts), such as 158, were prepared by using a one-pot protocol involving the enantioselective Mannich reaction of 157 catalyzed by 2 n, followed by a Horner olefination (Scheme 97). [126] Jørgensen and co-workers reported an asymmetric monofluorovinylation through an enantioselective Mannich reaction of a-fluoro-b-keto-benzothiazolesulfone, such as 159, with in situ generated N-benzyloxycarbonylimine (N-Cbz-imine) in the presence of catalyst 2 o. Reduction of the Mannich product with LiBH 4 gave (E)-160 with good enantioselectivity (Scheme 98).…”
Section: à C Bond Formationmentioning
confidence: 99%
“…Aza-Morita-Baylis-Hillman adducts were also obtained via a one-pot Horner-type olefination in combination with a Mannich reaction (Scheme 32). 63 In this context, Bernardi, Ricci and co-workers demonstrated that good yields and excellent enantioselectivities were observed through this process in the presence of phase-transfer catalyst 10a. O O R 3 O R 3 O R 1 = M e , O R R 2 = a l k y l R 3 = pt o l y l , 2 -t r i m e t h y l s i l y l e t h y Alternatively to Mannich reactions, the [4+2] cycloadditions of ketenes and imines can be used in the construction of Mannich-type adducts, such as b-amino carbonyl compounds.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…158, wurden in einer Eintopfreaktion durch enantioselektive Mannich-Reaktion von 157 in Gegenwart des Katalysators 2 n und nachfolgende Horner-Olefinierung hergestellt (Schema 97). [126] Jørgensen et al berichteten über eine asymmetrische Monofluorvinylierung durch enantioselektive Mannich-Reaktion des a-Fluor-b-ketobenzothiazolsulfons 159 mit in situ hergestelltem N-Benzyloxycarbonyl(N-Cbz)-Imin in Gegenwart des Katalysators 2 o. Die Reduktion des Mannich-Produkts mit LiBH 4 führte mit guter Enantioselektivität zu E-160 (Schema 98).…”
Section: Phasentransferreaktionenunclassified